Genome-wide association study for yield-related traits in faba bean (Vicia faba L.) - Gutierrez, Natalia; Pégard, Marie; Solis, Ignacio; Sokolovic, Dejan; Lloyd, David; Howarth, Catherine; Torres, Ana M. (Frontiers in Plant Science, 2024)
Yield is the most important and complex trait to improve crop production and identifying the genetic determinants for high yield is a major issue to breed new varieties. In faba bean (Vicia faba L.), quantitative trait loci (QTLs) have previously been detected from in studies of biparental mapping populations, but the genes controlling the main trait components remain largely unknown. The aim of In this study was towe investigated for the first time the genetic control of six faba bean yield related traits: shattering (SH), pods per plant (PP), seeds per pod (SP), seeds per plant (SPL), 100 seed weight (HSW) and plot yield (PY), using a genomewide association study (GWAS) on a worldwide collection of 352 homozygous faba bean accessions with the aim of identifying markers associated with them. Phenotyping was carried out in field trials at three locations (Spain, United Kingdom and Serbia) over 2 years. The faba bean panel was genotyped with the Affymetrix faba bean SNP-chip yielding 22.,867 SNP markers. T and the GWAS analysis identified 112 97 significant marker trait associations (MTAs) in 97 candidate genes, distributed over the six faba bean chromosomes. Eight MTA were detected in at least two environments and five were associated with multiple traits. These candidates A next step will be to validated to these candidates estimate their effects in different genetic backgrounds and to provide resources for marker assisted breeding of faba bean yield.